Emerging and Endemic Pathogens Advances in Surveillance, Detection and Identification - O'Connell, Kevin P.; Skowronski, Evan W.; Sulakvelidze, Alexander; Bakanidze, Lela.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This volume highlights recent advances in the tracking, detecting, and identifying of emerging and endemic pathogens throughout the world. The authors of the chapters are among the foremost experts in epidemiology, microbiology and public health and leaders in their respective countries. The chapters offer views on the history and current state of disease surveillance with special emphasis on the Caucasus and Central Asia, the historical land bridge between Europe and Asia through which epidemics have passed throughout history. A must-read for both specialists and students in public health.
Keynotes Contribution -- Global Effect and Prevention of Emerging and Epidemic Pathogens: Cholera and Citrus Greening as Examples -- Surveillance -- The Epidemiological Surveillance of Highly Pathogenic Diseases in Kazakhstan -- Surveillance on Plague in Natural Foci in Georgia -- Application of Modern Techniques for Studying Bacterial Pathogens in Georgia -- Especially Dangerous Infections in Azerbaijan -- Strengthening the Early-Warning Function of the Surveillance System: The Macedonian Experience -- Integrating Geographic Information Systems and Ecological Niche Modeling into Disease Ecology: A Case Study of Bacillus anthracis in the United States and Mexico -- Molecular Analysis and Tools -- Applications of Paleomicrobiology to the Understanding of Emerging and Re-emerging Infectious Diseases -- Characterization of a Putative Hemagglutinin Gene in the Caprine Model for Brucellosis -- Pathoadaptation of Especially Dangerous Pathogens -- Detection of Pathogens Via High-Throughput Sequencing -- Environmental Influences on the Relative Stability of Baculoviruses and Vaccinia Virus: A Review.
Keywords: Life sciences; Epidemiology; Microbiology; Microbial genetics; Life Sciences; Microbiology; Public Health/Gesundheitswesen.; Environmental Monitoring/Analysis.; Microbial Genetics and Genomics; Epidemiology